O, N co-doped porous activated carbon from polyvinyl chloride for super capacitors and solar cells application - Pawan Singh Dhapola; Sushant Kumar; Manoj Karakoti; M.Z.A. Yahya; Vinay Deep Punetha; Sandeep Pandey; Faisal Islam Chowdhury; Serguei V. Savilov; Pramod K. Singh (Chemical Physics Impact)
Porous-activated carbons (PAC) show a lot of applications in various fields due to their large surface area and appropriate pore volume, along with decent thermal, chemical, and mechanical stability. Because of these characteristics, PACs are the best choice as an electrode material in supercapacitors (SCs). Due to the utility of PACs, this work reports the transformation of polyvinyl chloride (PVC) into PAC with a surface area of 162.40 m2/g. The synthesized PAC exhibits a maximum specific capacitance (CSP) of 40 F/g at five mV/s in 1-ethyl-3- methylimidazolium thiocyanate ionic liquid (EMIM SCN-IL) electrolyte. Also, no degradation was recorded in the initial Csp of the fabricated SC, even after 9000 cycles at room temperature. Additionally, using the same PAC in counter electrode dye-sensitized solar cell (DSSC) was also fabricated, and the cell was tested at 1 sun condition, which shows a fill factor of 59.37 % and an efficiency of 1.42 %.